Effects of Fill Volume and Humidification on Aerosol Delivery During Single-Limb Noninvasive Ventilation. - Saeed, Haitham; Mohsen, Marwa; Eldin, Abeer Salah; Elberry, Ahmed A.; Hussein, Raghda R. S.; Rabea, Hoda; Abdelrahim, Mohamed E. A. (Respiratory Care, 2018)
BACKGROUND: The aim of this work was to determine the effect of fill volume and humidification change on aerosol delivery during single-limb noninvasive ventilation (NIV). METHODS: Four groups were recruited, each consisting of 12 subjects (6 females) with COPD receiving NIV. Groups 1 and 3 received inhaled salbutamol with a vibrating mesh nebulizer, and Groups 2 and 4 received inhaled salbutamol with a jet nebulizer. The in vivo study was carried out on days 1 and 3. In groups 1 and 2, 2 fill-volumes were delivered to each subject; 1 mL 5,000 µg/mL salbutamol respirable solution used as it is or diluted to a total of 2 mL using normal saline. In groups 3 and 4, 1 mL 5,000 µg/mL salbutamol respirable solution diluted to 2 mL total volume using normal saline was delivered to each subject with and without humidification. Unchanged salbutamol in urine at 30 min (USAL0.5) and in pooled urine at 24 h (USAL24) was determined. On day 2, the ex vivo study was carried out on subjects using the same experimental setting with a filter placed proximal to their face mask for collection of total inhaled dose of salbutamol (aerosol emitted). RESULTS: The vibrating mesh nebulizer delivered higher USAL0.5, USAL24, and aerosol emitted compared to the jet nebulizer at all fill volumes and humidification conditions (P < .001). Increasing fill volume from 1 mL to 2 mL resulted in a significant increase in USAL0.5, USAL24, and aerosol emitted from the jet nebulizer (P < .05) with an insignificant effect on the vibrating mesh nebulizer. A 2-mL fill volume with the jet nebulizer delivered USAL24 and aerosol emitted comparable to those of 1 mL with the vibrating mesh nebulizer with significantly longer nebulization times (P < .001). Humidification had an insignificant effect on aerosol delivery. CONCLUSIONS: Increasing the fill volume of a jet nebulizer is essential to increase the amount of inhaled medication reaching a subject. In contrast, there is no need to increase fill volumes when using a vibrating mesh nebulizer. There is no need to switch off the humidifier while delivering aerosol through a singlelimb NIV circuit.